Chemical, Microbiological and Sensorial Properties of Tulum Cheese - Adiguzel, Gulsah; Atasever, Mustafa; Karakaya, Yakup; Aydemir, Meryem; Unsal, Cemal (Asian Journal of Chemistry, 2010)
This study was carried out to determine the chemical, microbiological and sensorial properties of Tulum cheese, a raw milk cheese. 50 Randomly selected samples of Tulum cheese purchased from different retail markets in Erzurum and Konya regions, were analyzed. The production technique of Tulum cheese was investigated too. It was found that chemical, microbiological and sensorial properties of the samples varied in large range; especially microbiological quality was not very good. It is concluded that it is necessary to undertake hygienic measurements and use heat-treated milk in production and further investigations are required for standardizing the production technique of Tulum cheese.